Challenges and Strategies for Implementing Qualified Refundable Tax Credit in Indonesia - SIDIQ, Muhamad Abdulrahman; SUPRIYADI, Supriyadi (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the policy-making process, challenges, and implementation strategies of the Qualified Refundable Tax Credit (QRTC) in Indonesia. The theories used are public policy, public policy implementation, and global minimum tax. The research method used is qualitative with a narrative approach. Primary data sources were obtained through interviews with policy makers, academics, and tax practitioners. Secondary data sources were obtained through literature reviews. The results of this study indicate that the Qualified Refundable Tax Credit is implemented as an addition to GloBE profits, so it is not very significant in reducing effective tax rates. The challenges and strategies for implementing the Qualified Refundable Tax Credit consist of communication, resources, disposition, and bureaucratic structure aspects. This study can be used as input for policymakers in implementing the Qualified Refundable Tax Credit in Indonesia.